Gamifying rehabilitation: MILORD platform as an upper limb motion rehabilitation service - Fotopoulos, Dimitris; Ladakis, Ioannis; Kilintzis, Vassilis; Chytas, Achilleas; Koutsiana, Elisavet; Loizidis, Theodoros; Chouvarda, Ioanna (Frontiers in Computer Science, 2022)
Motor learning is based on the correct repetition of specific movements for their permanent storage in the central nervous system (CNS). Rehabilitation relies heavily on the repetition of specific movements, and game scenarios are ideal environments to build routines of repetitive exercises that have entertaining characteristics. In this respect, the gamification of the rehabilitation program, through the introduction of game-specific techniques and design concepts, has gained attention as a complementary or alternative to routine rehabilitation programs. A gamified rehabilitation program promises to gain the patient’s attention, to reduce the monotony of the process and preserve motivation to attend, and to create virtual incentives through the game, towards maintaining compliance to the ‘prescribed’ program. This is often achieved through goal-oriented tasks and real-time feedback in the form of points and other in-game rewards. This paper describes MILORD rehabilitation platform, an affordable technological solution which aims to support health professionals and enable remote rehabilitation, while maintaining health service characteristics and monitoring. MILORD is an end-to- end platform that consists of an interactive computer game, utilizing Leap Motion sensor, a centralized user management system, an analysis platform that processes the data generated by the game, and an analysis dashboard presenting a set of meaningful features that describe upper limb movement. Our solution facilitates the monitoring of the patients' progress and provides an alternative way to analyze hand movement. The system was tested with normal subjects and patients as well as experts to record user experience, receive feedback, identify any problems, and understand the system’s value in monitoring and support motion defect and progress. This small-scale study indicated the capacity of the analysis to quantify the movement in a meaningful way and express differences between normal and pathological movement, and the user experience was positive both with patients and normal subjects.